Ferroptosis and hepatocellular carcinoma: the emerging role of lncRNAs - Chen, Haoran; Han, Zhongyu; Su, Junyan; Song, Xuanliang; Ma, Qingquan; Lin, Yumeng; Ran, Zijin; Li, Xueping; Mou, Rongkun; Wang, Yi; Li, Dongxuan (Frontiers in Immunology, 2024)
Hepatocellular carcinoma is the most common form of primary liver cancer and poses a significant challenge to the medical community because of its high mortality rate. In recent years, ferroptosis, a unique form of cell death, has garnered widespread attention. Ferroptosis, which is characterized by iron-dependent lipid peroxidation and mitochondrial alterations, is closely associated with the pathological processes of various diseases, including hepatocellular carcinoma. Long non-coding RNAs (lncRNAs), are a type of functional RNA, and play crucial regulatory roles in a variety of biological processes. In this manuscript, we review the regulatory roles of lncRNAs in the key aspects of ferroptosis, and summarize the research progress on ferroptosis-related lncRNAs in hepatocellular carcinoma.